Accurate PIV measurement on slip boundary using single-pixel algorithm. (1st May 2022) - Li, Hongyuan; Cao, Yufan; Wang, Xiangyu; Wan, Xia; Xiang, Yaolei; Yuan, Huijing; Lv, Pengyu; Duan, Huiling
Abstract: To accurately measure the near-wall flow by particle image velocimetry (PIV) is a big challenge, especially for the slip boundary condition. Apart from high-precision measurements, an appropriate PIV algorithm is important to resolve the near-wall velocity profile. In our study, the single-pixel algorithm is employed to calculate the near-wall flow, which is demonstrated to be capable of accurately resolving the flow velocity near the slip boundary condition. Based on synthetic particle images, the advantages of the single-pixel algorithm are manifested in comparison with the conventional window-correlation algorithm. In particular, the single-pixel algorithm has higher spatial resolution and accuracy, and lower systematic error and random error for the case of the slip boundary condition. Furthermore, for experimental verification, micro-PIV measurements are conducted over a liquid–gas interface, and the single-pixel algorithm is successfully applied to the calculation of near-wall velocity under the slip boundary condition, especially negative slip velocity. The current work demonstrates the advantages of the single-pixel algorithm in analyzing complex flows under the slip boundary condition, such as in drag reduction, wall skin-friction evaluation, and near-wall vortex structure measurement.